Meaning in life experienced by parents of children living with diabetes. Issue 1 (March 2019) - Bekker, Christiaan I; Deacon, Elmari; Segal, David
In this study, nine parents of children living with well-controlled diabetes participated in semi-structured interviews to explore how they make meaning of living with a child with diabetes. Creating a state of normalcy that incorporates the diabetes care plan, empowering their children to successful transition to independent care, positive relationships with their medical team as well as acquiring and sharing diabetes-related knowledge and skills add to the meaning in life of these parents. Health practitioners should facilitate conversations with parents to help them realise their motivation for adhering to the diabetes care plan.